RNA and protein immunization with Trypanosoma cruzi trans-sialidase containing SAPA repeats protects mice against infection and promotes a balanced inflammatory response - dos Santos, Nailma Silva Aprigio; de Almeida-Júnior, Carlos Roberto; Ricci, Mayra Fernanda; Sanches, Rodrigo C. O.; Fernandes, Renata Salgado; Burle-Caldas, Gabriela de A.; de Castro, Júlia Teixeira; Reis-Cunha, João Luís; Bartholomeu, Daniella C.; Meira, Ana Clara Martins; Nascimento, Thaiane Gomes; Oliveira, Natalia Fernanda de Melo; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Proteins with repeat domains are commonly found in protozoan parasites. Trypanosoma cruzi, which causes Chagas disease (CD), possesses a group of surface proteins called trans-sialidases (TS). These proteins are responsible for transferring sialic acid from the host’s glycoconjugates to the parasite’s mucins. The TS proteins feature a C-terminal immunogenic domain that includes amino acid repeats known as SAPA (Shed Acute Phase Antigen). Shed in the blood of the infected host, TS mediates several biological effects and because of its essential role during infection, it has been tested recurrently as a vaccine candidate against CD. Here, we investigate the effect of immunizing mice with recombinant TS proteins with and without (w/o) SAPA repeats, as well as with a protein containing only the repeat domain. We also immunize mice with RNA formulations encoding TS sequences with and without SAPA. Besides confirming the immunodominance of the SAPA domain, after challenging immunized animals with T. cruzi, we showed that the presence of the repeats did not significantly impact protection and parasite numbers after infection. However, immunization with TS protein or RNA containing the repeat domain resulted in increased production of IL-10 compared to mice immunized with TS without SAPA, and this increased IL-10 production correlates with a significant reduction in the inflammatory infiltrate in heart tissues of infected animals. These results indicate that the immunodominant SAPA domain plays a role in promoting an anti-inflammatory response, which, as a vaccine component, may contribute to induce a desirable, more balanced immune response.